1990
DOI: 10.1017/s0043174500056332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additives on the Efficacy, Uptake, and Translocation of the Methyl Ester of Thifensulfuron

Abstract: Effects of a 28% N solution containing urea and ammonium nitrate (28% UAN) on field efficacy of the methyl ester of thifensulfuron and combinations of thifensulfuron and the methyl ester of chlorimuron were investigated. Velvetleaf control and soybean injury increased as rates of thifensulfuron increased (0, 2.2, 4.4, and 5.8 g ai/ha) and as rates of chlorimuron increased (0, 4.4, and 8.8 g ai/ha). Treatments that included 28% UAN at 9 L/ha controlled velvetleaf 9% better, averaged across herbicides and rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…On the basis of reports of efficacy in the literature, it was expected that velvetleaf seedling mortality would be much greater (70 to 100%) than that observed here (Buhler et al 1990;Fielding and Stoller 1990;Hart and Penner 1993;Jordan et al 1997;Krausz et al 1995;Mills and Witt 1989;Niekamp and Johnson 2001). The reason for reduced mortality may be that these experiments were conducted in the absence of competition from the crop.…”
Section: Mortalitymentioning
confidence: 68%
“…On the basis of reports of efficacy in the literature, it was expected that velvetleaf seedling mortality would be much greater (70 to 100%) than that observed here (Buhler et al 1990;Fielding and Stoller 1990;Hart and Penner 1993;Jordan et al 1997;Krausz et al 1995;Mills and Witt 1989;Niekamp and Johnson 2001). The reason for reduced mortality may be that these experiments were conducted in the absence of competition from the crop.…”
Section: Mortalitymentioning
confidence: 68%
“…The weed control spectrum of thifensulfuron may be broadened with fertilizer solutions such as a 28% N solution containing urea and ammonium nitrate (UAN) as a spray additive. Fielding and Stoller (1990) reported increased velvetleaf (Abutilon theophrasti Medik.) con-trol with the addition of 28% UAN to thifensulfuron applied with X-77 NIS at 0.25% v/v.…”
Section: Introductionmentioning
confidence: 99%
“…The most plausible explanation for increased injury is presence of VAN. Fielding and Stoller (1990) reported that the addition of V AN to thifensulfuron resulted in greater injury to soybean compared to thifensulfuron applied alone.…”
mentioning
confidence: 99%
“…V rea ammonium nitrate was not applied when herbicides were applied alone. Fielding and Stoller (1990) Influence ofProhexadione Calcium on Herbicide Efficacy. The interaction ofexperiment by herbicide and the main effect ofprohexadione calcium were significant for pitted morningglory control.…”
mentioning
confidence: 99%